Muslim women in politics: does it align with Shari‘ah parameters? - Mahmad Robbi, Ahmad Akram; Mohd Yunus, Saidatolakma; Mohamad Sharin, Mohamad Faiq (IIUM Press, 2023)
This study aims to identify the practice of Muslim women in politics according to Shari‘ah principles and Malaysian perspective on their involvement as this country has adopted democracy which allows women to get involved in politics. Generally, there are at least two opinions found in the literature where there are scholars who have decisively opposed women from positioning themselves in politics i.e: head of a state and others permit their grant for women to involve in politics. This study is applying the qualitative methodology in which the authors tend to get information directly from the primary sources as well as the secondary booked by both traditional and modern scholars related to the field of this study. All the information gathered in the books does seem important to the authors as it denotes the idea of the topic clearly from the illustrated interpretations. As a result, the authors find that there is no harm for Muslim women to involve in the political area. Despite the permission, Malaysia still struggling to empowering women’s will as noted in National Women’s Policy Malaysia which to provide encouragement for women’s involvement in politics by targeting 30 percent of their involvement.